Three‐dimensional mapping of crystalline ceramic waste form materials. Issue 8 (21st April 2017) - Cocco, Alex P.; DeGostin, Matthew B.; Wrubel, Jacob A.; Damian, Peter J.; Hong, Tao; Xu, Yun; Liu, Yijin; Pianetta, Piero; Amoroso, Jake W.; Brinkman, Kyle S.; Chiu, Wilson K. S.
Abstract: This work demonstrates the use of synchrotron‐based, transmission X‐ray microscopy (TXM) and scanning electron microscopy to image the 3‐D morphologies and spatial distributions of Ga‐doped phases within model, single‐ and two‐phase waste form material systems. Gallium doping levels consistent with those commonly used for nuclear waste immobilization (e.g., Ba1.04 Cs0.24 Ga2.32 Ti5.68 O16 ) could be readily imaged. The analysis suggests that a minority phase with different stoichiometry/composition from the primary hollandite phase can be formed by the solid‐state ceramic processing route with varying morphology (globular vs. cylindrical) as a function of Cs content. The results presented in this work represent a crucial step in developing the tools necessary to gain an improved understanding of the microstructural and chemical properties of waste form materials that influence their resistance to aqueous corrosion. This understanding will aid in the future design of higher durability waste form materials.